2021
DOI: 10.1016/j.heliyon.2021.e08151
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of CAD-CAM monolithic systems compared: three multi-layered zirconia and one lithium disilicate system

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 48 publications
4
9
0
1
Order By: Relevance
“…The results of the present study also showed a significant difference in translucency between IPS e.max CAD and Katana zirconia UTML after cementation and after aging. This finding is supported by previous studies 9,10,14 . The least observed change in translucency was found in Katana zirconia.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study also showed a significant difference in translucency between IPS e.max CAD and Katana zirconia UTML after cementation and after aging. This finding is supported by previous studies 9,10,14 . The least observed change in translucency was found in Katana zirconia.…”
Section: Discussionsupporting
confidence: 93%
“…Various ceramic systems such as lithium disilicate, lithium disilicate derivatives, and zirconium oxide ceramics have been introduced to the dental market [7][8][9][10] . The unique microstructure of lithium disilicate ceramics plays a key role in its mechanical and optical properties [11][12][13][14] .…”
mentioning
confidence: 99%
“…Another possibility is pressing fluorapatite glass-ceramic ingots onto CAD/CAM milled zirconia frameworks: IPS e.max ZirPress (Ivoclar Vivadent, Schaan, Liechtenstein), which allows pressing onto IPS e.max ZirCAD (Ivoclar Vivadent, Schaan, Liechtenstein), Zenostar Wieland Dental (Pforzheim, Germany), and other zirconia frameworks with a CTE of 10.5-11.0. The press-on technique is indicated for multi-unit bridges and crowns and implant superstructures [38][39][40].…”
Section: Zirconia-based Polycrystalline Ceramicsmentioning
confidence: 99%
“…6 Various ceramic systems such as lithium disilicate, lithium disilicate derivatives, and zirconium oxide ceramics have been introduced to the dental market. [7][8][9][10] The unique microstructure of lithium disilicate ceramics plays a key role in its mechanical and optical properties. [11][12][13][14] Ceramic laminate veneers, if properly bonded, become an integral part of tooth structure and share a portion of the applied load during chewing cycles.…”
Section: Introductionmentioning
confidence: 99%